Analysis of Cloud Computing Information Security Strategy in Biznet Networks - Heri Sutrisno (Department of Electrical Engineering, 2013)
Information security on cloud computing requires goodplanning and understanding of the risks, threats and vulnerabilities ofdata or information that is managed in a cloud computing environment.Measurement of information security in cloud computing is no differentto conventional information technology, which uses an approach basedon confidentiality, integrity and availability of information. Whereas thestandard used on information security such as NIST, CSA and COBITare often used to assess information security analysis of the cloudcomputing service providers. This research will review the informationsecurity strategy at Biznet Networks as a provider of cloud computingservices.